Lessons of Spanish substantive criminal law - Prieto del Pino, Ana María (Cizur Menor, Navarra Aranzadi, 2017)
The main purpose of this book is to fill an existing gap by providing Spanish law students with an updated comprehensive overview of the scope of application of the Spanish substantive criminal law. Therefore, topics belonging to the field of international procedural cooperation, such as extradition and the European arrest warrant have been omitted entirely. Basic concepts relating to issues such as the role of criminal law and its legitimating principles, the theories of punishment, security measures, the sources of the Spanish substantive criminal law as well as the temporal and spatial scope thereof are addressed in considerable depth. Notwithstanding this, given that it has been conceived as a course-book, footnotes have not been used in order to render the text easier to read. A final self-assessment multiple choice quiz section and an appendix containing the right answers have been included, so that students themselves can test the level of knowledge acquisition they have reached. Moreover, this book aims to be a useful tool for Spanish scholars and legal practitioners in order to improve their ability to use English in both academic and professional contexts and to increase their knowledge of this language in the field of criminal law. Another purpose of this work is to provide foreign scholars and law professionals with a starting point for researching Spanish substantive criminal law.
Keywords: Derecho penal